Idea Structural Analysis Of Dictionary: Lexicographic Study On Al-Mu’jam Al-Wajīz : At-Tahlīl al-Binyawī li al-Afkār fī al-Ma‘ājim: Dirāsah Ma‘ājimiyyah li Kitāb al-Mu‘jam al-Wajīz - Moh. Iza Al Jufri; Saddam Reza Hamidi (An-Nahdah Al-'Arabiyah, 2025)
In The era of information technology, dictionaries play an important role in language studies, including Al-Mu’jam Al-Wajīz. This dictionary has an important role, especially in the study of Arabic terms in the modern era. The aims of this research are: First, what is the identity and typology of Al-Mu’jam Al-Wajīz. Second, what are the completeness components of the dictionary in Al-Mu’jam Al-Wajīz. This study uses a qualitative descriptive approach. Primary data were obtained from Al-Mu’jam Al-Wajīz, while secondary data came from lexicography books, research journals, theses, and other relevant scientific articles. Data collection techniques were carried out through reading and recording sources related to the research topic. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of this research are based on an analysis of the completeness component of Dr. Ali Al-Qasimy revealed that Al-Mu’jam Al-Wajīz has fulfilled 21 components of the 27 components of the completeness of the dictionary. This shows that most of the completeness components of Al-Mu’jam Al-Wajīz have been fulfilled and can be said to have an ideal dictionary structure. This research can be used as reference material, notes or comparisons for developments in compiling Arabic dictionaries in the modern era. في عصر تكنولوجيا المعلومات، تلعب المعاجم دورًا مهمًا في دراسة اللغة، بما في ذلك المعجم الوجيز. ويحتل هذا المعجم مكانة بارزة، خاصة في دراسة المصطلحات العربية في العصر الحديث. تهدف هذه الدراسة إلى: أولًا، تحديد هوية ونمط المعجم الوجيز. ثانيًا، تحليل مكونات اكتمال المعجم في المعجم الوجيز. تعتمد هذه الدراسة على منهج وصفي نوعي. تم الحصول على البيانات الأولية من المعجم الوجيز، بينما جاءت البيانات الثانوية من كتب المعاجم، والمجلات البحثية، والرسائل العلمية، والمقالات العلمية الأخرى ذات الصلة. تم جمع البيانات من خلال القراءة وتسجيل المصادر المتعلقة بموضوع البحث. وتم تحليل البيانات عبر مراحل تقليل البيانات، وعرض البيانات، واستخلاص النتائج. كشفت نتائج هذه الدراسة، بناءً على تحليل مكونات اكتمال المعجم وفقًا للدكتور علي القاسمي، أن المعجم الوجيز قد استوفى 21 مكونًا من أصل 27 مكونًا من مكونات اكتمال المعجم. وهذا يدل على أن معظم مكونات اكتمال المعجم الوجيز قد تحققت، مما يجعله معجمًا ذا هيكل مثالي. يمكن أن تُستخدم هذه الدراسة كمصدر مرجعي أو ملاحظات أو مقارنة لتطوير إعداد المعاجم العربية في العصر الحديث. Dalam era teknologi informasi, kamus memainkan peran penting dalam kajian bahasa, termasuk Al-Mu’jam Al-Wajīz. Kamus ini memiliki peran yang signifikan, terutama dalam studi istilah-istilah Arab di era modern. Penelitian ini bertujuan untuk: Pertama, mengidentifikasi identitas dan tipologi Al-Mu’jam Al-Wajīz. Kedua, menganalisis komponen kelengkapan kamus dalam Al-Mu’jam Al-Wajīz. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data primer diperoleh dari Al-Mu’jam Al-Wajīz, sedangkan data sekunder berasal dari buku-buku leksikografi, jurnal penelitian, tesis, dan artikel ilmiah lain yang relevan. Teknik pengumpulan data dilakukan melalui membaca dan mencatat sumber-sumber yang berkaitan dengan topik penelitian. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini, berdasarkan analisis komponen kelengkapan kamus menurut Dr. Ali Al-Qasimy, mengungkapkan bahwa Al-Mu’jam Al-Wajīz telah memenuhi 21 dari 27 komponen kelengkapan kamus. Hal ini menunjukkan bahwa sebagian besar komponen kelengkapan dalam Al-Mu’jam Al-Wajīz telah terpenuhi, sehingga dapat dikatakan memiliki struktur kamus yang ideal. Penelitian ini dapat dijadikan sebagai bahan referensi, catatan, atau perbandingan dalam pengembangan penyusunan kamus bahasa Arab di era modern.